Promotion mechanism of hydroxyl groups in catalyzing CO2 cycloaddition - Yiming Wang; Wensheng Wei; Yuxin Wang; Guangwen Xu; Jinggang Zhao; Lei Shi (Journal of CO2 Utilization)
In this study, a series of hydroxy-functionalized quaternary ammonium salt catalysts, i.e., NEt3(HE)Br, NEt2(HE)2Br, NEt1(HE)3Br, and N(HE)4Br, were successfully prepared by quantitatively grafting hydrogen-bond donors (HBDs) as electrophilic sites on quaternary ammonium salts and then used to catalyze the cycloaddition of propylene oxide (PO) and carbon dioxide (CO2). The aim was to reveal the effects of different amounts of hydroxy-functionalized quaternary ammonium salts on their catalytic activities. The synergistic catalytic effect of NEt3(HE)Br and a biomass-based catalytic system (NEt3(HE)Br/Bio) on the cycloaddition reaction was systematically studied, and the influence mechanism of hydroxy-rich biomass on the cycloaddition reaction was elucidated. The promoting effects of the hydroxyl-group content, position and connection structure in different alcohol additives on the CO2 cycloaddition reaction were further investigated and the results demonstrated that when the additive molecule contains an appropriate number of ortho-hydroxyl groups and these hydroxyl groups are connected to groups with strong electron-withdrawing ability and small steric hindrance, the cycloaddition efficiency between PO and CO₂ can be significantly enhanced. The reason is that these hydroxyl groups not only provide more hydrogen bonds, enhancing the intermolecular interactions, but also help to stabilize the transition state of the reaction. Notably, when 0.48 g of NEt3(HE)Br was mixed with 0.48 g of cellulose as HBDs to catalyze the cycloaddition reaction of CO2 and PO, PO conversion reached 99.34 % within 2 h, exceeding that obtained with the catalytic reaction system without HBDs. In addition, the NEt3(HE)Br/cellulose catalytic system was demonstrated to be universal for catalyzing the cycloaddition reaction of different epoxides and CO2. This article provides theoretical guidance and new inspirations for the efficient utilization of hydroxy-containing biomass materials in CO2 conversion.